Bax Exists in a Dynamic Equilibrium between the Cytosol and Mitochondria to Control Apoptotic Priming - Schellenberg, Barbara (Cell Press, 2013)
The proapoptotic Bcl-2 protein Bax is predominantly found in the cytosol of nonapoptotic cells and is commonly thought to translocate to mitochondria following an apoptotic stimulus. The current model for Bax activation is that BH3 proteins bind to cytosolic Bax, initiating mitochondrial targeting and outer-membrane permeabilization. Here, we challenge this and show that Bax is constitutively targeted to mitochondria but in nonapoptotic cells is constantly translocated back to the cytosol. Using live-cell spinning-disk confocal imaging with a combination of FLIP, FRAP, and photoactivatable GFP-Bax, we demonstrate that disrupting adhesion-dependent survival signals slows the rate of Bax’s dissociation from mitochondria, leading to its accumulation on the outer mitochondrial membrane. The overall accumulation of mitochondrial Bax following loss of survival signaling sensitizes cells to proapoptotic BH3 proteins. Our findings show that Bax is normally in a dynamic equilibrium between cytosol and mitochondria, enabling fluctuations in survival signals to finely adjust apoptotic sensitivity.